Higher education administration with social media - Wankel, Laura A.; Wankel, Charles (Bingley, U.K. : Emerald, 2011)
New technologies provide new ways of delivering the programs and services of higher educational (HE) institutions. Social media such as Facebook, blogs, Flickr, Twitter, and the Second Life virtual world engage constituents and enhance effectiveness. Understanding the trends in the expanding role of social media in HE and the related implications for staff preparedness and training is necessary for future-oriented administrators and practitioners. This book examines how social media are redefining what university communities are and the purposes and practices of the various functional areas in HE. It presents an overview of innovative practices in the recruitment, advising, retention, graduation and engagement of students and alumni, and examines social media in connection with enrollment management, advising and mentoring, public relations and alumni relations. Topics covered include: how Facebook helps and hinders students social integration; connecting fans and sports more intensively through social media; how to prepare staff to use social media in robust ways; and using social networking sites during the career management process, for social research and studying abroad.
Connecting on campus with new media : introduction to higher education administration with social media / Laura A. Wankel, Charles Wankel -- Hybrid engagement : how Facebook helps and hinders students' social integration / Bree McEwan -- Social media for social research : applications for higher education communications / Nicolle Merrill -- Social media use by enrollment management / Phillip Griffiths, Anthony Wall -- Second life : the future of education is here today / P. Charles Livermore -- Mentoring 2.0 : high tech/high touch approaches to foster student support and development in higher education / Melanie Booth, Arthur Esposito -- Learning together : using social media to foster collaboration in higher education / Neil Ford, Melissa Bowden, Jill Beard -- Using social media in study abroad / Penny Schouten -- Using social networking sites during the career management process / Nancy Richmond, Beth Rochefort, Leslie Hitch -- Amplification and analysis of academic events through social media : a case study of the 2009 Beyond the Repository Fringe event / Nicola Osborne -- Connecting fans and sports more intensively through social media / Karen Weaver -- Engaging alumni and prospective students through social media / Eric Kowalik -- Am I invited? : social media and alumni relations / Heather Makrez -- Twitter in higher education : from application to alumni relations / Jon Hussey.
Includes index.
Print version record
Keywords: Education -- General; Education -- Administration -- General; Education; Organization & management of education; Education, Higher; Social media